2017
DOI: 10.1186/s12935-017-0427-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of VEGFR2 protein in HER2 positive primary human breast cancer: potential relevance to anti-angiogenic therapies

Abstract: BackgroundClinically relevant predictive biomarkers to tailor anti-angiogenic therapies to breast cancer (BRC) patient subpopulations are an unmet need.MethodsWe analyzed tumor vascular density and VEGFR2 protein expression in various subsets of primary human BRCs (186 females; Mean age: 59 years; range 33–88 years), using a tissue microarray. Discrete VEGFR2+ and CD34+ tumor vessels were manually scored in invasive ductal, lobular, mixed ductal-lobular and colloid (N = 139, 22, 18, 7) BRC cores.ResultsThe obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Also, our study confirmed that high VEGFR2 expression was associated with later TNM stage, which might suggest that VEGFR2 was essential for ESCC progression. Some studies have higher VEGFR2 expression was associated with worse overall survival of malignancies [31,32]. Then, we revealed that apatinib (highly selective VEGFR2 antagonist) inhibited the growth of human esophageal cancer cells in a time-and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 89%
“…Also, our study confirmed that high VEGFR2 expression was associated with later TNM stage, which might suggest that VEGFR2 was essential for ESCC progression. Some studies have higher VEGFR2 expression was associated with worse overall survival of malignancies [31,32]. Then, we revealed that apatinib (highly selective VEGFR2 antagonist) inhibited the growth of human esophageal cancer cells in a time-and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 89%
“…These data imply that the effects of HER2 on tumorigenesis are at least partially mediated by stimulation of angiogenesis, which provides a strong rationale for targeting the VEGF/VEGFR2 axis in HER2-positive breast cancer. 29 Based on this hypothesis, several clinical trials have been conducted to explore the potential benefit of anti-HER2 and anti-angiogenesis combination therapy for HER2-positive breast cancer. Results from early phase trials have been promising.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed a higher THC value in Ki67 index-high lesions, alas without statistical significance. With lesion size increasing from Stage T1 to Stages T2 and T3, THC increased along with Ki67 index; but no THC difference was found between T2 and T3 lesions, probably due to saturated blood supply when tumors grow to a certain large size, or to tumor heterogeneity [28] , we speculate. Using multiple regression analysis tool, we derived a formulation of THC = 167.2 + 1.062size+ 0.298ki67, to demonstrate a linear correlation of THC and its 2 most impacting factors lesion size and Ki67 index.…”
Section: Discussionmentioning
confidence: 69%